K-pop’s Overcrowded Market: Analyzing the Effects of Excessive Debuts on Industry Revenue and Growth - Jiaying Liu (Law and Economy, 2025)
The rapid expansion of K-pop has led to market oversaturation, where an increasing number of group debuts has fragmented revenue, intensified competition, and shortened artist careers. This paper examines the impact of excessive debuts on industry revenue and sustainability, highlighting the concentration of concert revenue among top-tier groups and the financial struggles of mid-tier and rookie artists. Additionally, it explores the decline in creative innovation due to mass production pressures. To address these challenges, the study proposes strategic solutions, including regulating debuts, extending promotional cycles, diversifying revenue streams, and encouraging artistic experimentation to ensure K-pop’s long-term growth and global influence.